PEMBUATAN WEBSITE PENJUALAN TOKO BAJU BIAZRA-STORE MENGGUNAKAN PHP DAN MYSQL - Apandi, Ahmad; Syalis Ibnih Melati Istini (Jurnal Teknik dan Science, 2023)
Advances in technology and information continue to develop very quickly without us realizing it, especially in the computer sector. Biazra-store is a shop that sells various types of clothing, Biazra-store currently does not have a website to market their sales. Currently, Biazra-store still uses a manual system in carrying out transactions, making it sometimes difficult for customers to carry out transactions. Biazra-store needs a website to market their products using the internet so that customers can easily make transactions. The aim of creating this website is to make it easier for Biazra-store to market its products, apart from that it also makes it easier for customers to carry out transactions online. The method used in creating this website is the System Development Life Cycle (SDLC) method. This website has been tested using the Blackbox Testing method. The test shows that the website has met the needs and is suitable for use.